PRAKTIK POLITIK UANG DI KOTA SERANG PROVINSI BANTEN - Liah Culiah; Agus Aan Dermawan (Res Justitia : Jurnal Ilmu Hukum, 2022)
The Regional Head Election (Pilkada) of Serang City in 2018 is the third batch of simultaneous local elections held simultaneously throughout Indonesia. The problems of the 2018 Regional Head Elections in Serang City, leaving various obstacles and weaknesses. One of them is related to the phenomenon of money politics. The focus of this research examines the monitoring of money politics practices in the 2018 regional elections in Serang City. The results of this study attempt to describe the supervision of money politics in Serang City in the 2018 regional elections by the Serang City Supervisory Committee (Bawaslu) which found that there were money politics practices carried out by sympathizers of the candidate pair team. The research method in this study uses a qualitative method approach